A Convenient Synthesis of 2-Imino-1,3-Thiazine-4-One Derivatives from the Reaction of Primary Amines and Phenyl Isothiocyanate in the Presence of Acryloyl Chloride - Zolali, Amin; Nasiri, Farough; Omid-Niakan, Sonia (Combinatorial Chemistry & High Throughput Screening, 2014)
An efficient, one-pot and three-component synthesis of biologically important heterocyclic compounds is described from the reaction of primary amines and phenyl isothiocyanate in the presence of acryloyl chloride at room temperature without the need to use any catalyst.
Keywords: 1